Pola Kunjungan Wisatawan Pada Daya Tarik Wisata Di Kawasan Sarbagita - Andrian, I Putu Dody; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2019)
In  this  research  aims  to the  pattern  of  tourists’ visit on  tourists  attraction in  the  area of Sarbagita.  This  reseach was carried out to find out the movement of tourists in visiting one to other tourist destinations which existed in the area of Sarbagita. This research was through several stages, namely: identification of characteristic of tourists who were visiting Sarbagita area and how about the pattern type of their visit. Next it was studying how the path of tourists’ movement who were visiting tourist attractions existed in Sarbagita area. Data collection technique was using observation, interview,  distribution  of 100 questionnaires, literature study and documentation. Informant determination technique was  using  accidental  sampling. The  result  of  research  showed  that  tourists who were visiting various tourist destinations existed in Sarbagita area with the highest number of visits was in tourist attraction of Tanah Lot, Uluwatu, Kuta Beach, Sanur Beach, Bedugul, Ceking Rice Terrace and Pandawa Beach. The pattern of tourists’ visit who were visiting Sarbagita area had 4 types of visits, namely the first wasm “Single  Destination With  or Without  side  Trips” , the second was  “Transit  Leg  and Circle  Tour  at a  Destination” ,  the  third  was “Circle  Tour  With  or Without  Multiple  Access ,  Egress  Points ;  Different  Itinerary  Styles  Possible  at   Different  Destination  Areas”, and the fourth was “Hub and Spoke Style”. Keywords: Tourists, Pattern, Visit, Tourist Destination, Area